Rehabilitation in Ataxia - Anupam Gupta; Navin B. Prakash; Hafis Rahman (Indian Journal of Physical Medicine & Rehabilitation, 2023)
Ataxic disorders are numerous and relatively uncommon. They can result in lesions in the cerebellum, spinal cord, thalamic nuclei, vestibular nuclei, cerebral white matter and sensory pathways. Ataxia can be acute, subacute or chronic onset and progressive in nature. As pharmacological treatment, especially in chronic and progressive ataxia, is efficient nor is generally effective in treating various issues, rehabilitation has an important role to play in alleviating symptoms and quality of life. Various rehabilitation strategies such as conventional physical and occupational therapy, gait training and coordination therapy have been used for a long time. In the last 3–4 decades, there has been an addition in the armamentarium of rehabilitation with the use of non-invasive brain stimulation, virtual reality, body weight support treadmill training and robotic gait training to improve various aspects of the illness. The current evidence with rehabilitation strategies is also insufficient, so further longitudinal studies with bigger sample size and specific goal-directed therapies are the need of the hour.